Pemerolehan Bahasa Kedua dan Pengajaran Bahasa dalam Pembelajaran BIPA - Maharani, Tisa; Astuti, Endang Setiyo (Jurnal Bahasa Lingua Scientia, 2018)
This study attempts to expose the common structural errors of second language acquisition in bahasa Indonesia for foreign speakers (BIPA) learning at the beginner level and also to expose the implications of the errors for learning. This research utilizes descriptive qualitative method by describing in depth the findings in data analysis. This qualitative research focuses on the analysis of sentence structure, clauses, phrases, and also morphological structures. By doing so, it is expected that typical errors can be identified. Furthermore, this research is expected to help teachers to become more aware of these errors since by identifying the most problematic errors, teachers are able to relate fundamental concepts of sentences as well as those related to their own understanding of linguistics concepts, language and BIPA teaching, and also learners understanding as the part of learning.